Development of Video-Based Interactive Learning Media to Improve Students' Critical Thinking Abilities - Imansyah, M. Nurr; Hasanah, Uswatun (Jurnal Ilmiah Mandala Education (JIME), 2024)
Research has been carried out to develop video-based learning media at SMKN 02 Dompu using Camtasia studio 8 software with the aim of facilitating the delivery of basic electricity and electronics material. The data was analyzed descriptively quantitative-qualitatively with the results: media experts obtained a feasibility percentage of 68%, material experts 97%, student responses 93%, pre-test questions 71%, and post-test questions 90%. Judging from the results of video-based learning media data analysis is said to be feasible by obtaining a valid, effective and practical score that meets the feasibility value. The conclusion of this research is that video-based learning media to improve students' critical thinking skills created using Camtasia Studio 8 is suitable for use as a teaching tool.